2022
DOI: 10.3389/fphys.2022.859305
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Transcriptome and the Metabolome Response to Dietary Astaxanthin in Exopalaemon carinicauda

Abstract: Astaxanthin (Axn), a feed additive, is becoming increasingly important for modulating the metabolism, growth, development, and reproduction of aquatic organisms in aquaculture. In this study, Exopalaemon carinicauda (E. carinicauda) is an economically important fishery species in China that has been found to exhibit increased body weight following Axn feeding as compared to a standard diet. The antioxidant, transcriptomic, and metabolomic analyses of the response of E. carinicauda after Axn feeding were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…It has been well confirmed that HUFAs can significantly affect fundamental membrane properties such as acyl chain order, fluidity, elastic compressibility, phase behavior and permeability [ 35 , 36 ] and play a beneficial role in stabilizing dynamic membranes [ 37 ], membrane organization and cell division [ 38 ]. Metabolomic analysis in the present study showed significantly lower levels of DHA and EPA in the SMF group compared with the SMS group, which is consistent with the result found in ridgetail white prawn ( Exopalaemon carinicauda ) [ 39 ] and Pacific white shrimp ( Litopenaeus vannamei ) [ 40 ]. Acyl-CoA Oxidase (Acox) is a key enzyme involved in the β-oxidation of fatty acids [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been well confirmed that HUFAs can significantly affect fundamental membrane properties such as acyl chain order, fluidity, elastic compressibility, phase behavior and permeability [ 35 , 36 ] and play a beneficial role in stabilizing dynamic membranes [ 37 ], membrane organization and cell division [ 38 ]. Metabolomic analysis in the present study showed significantly lower levels of DHA and EPA in the SMF group compared with the SMS group, which is consistent with the result found in ridgetail white prawn ( Exopalaemon carinicauda ) [ 39 ] and Pacific white shrimp ( Litopenaeus vannamei ) [ 40 ]. Acyl-CoA Oxidase (Acox) is a key enzyme involved in the β-oxidation of fatty acids [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, we found significantly higher levels of LysoPC in the SMS group than in the SMF group. Lecithin (PC), cephalexin (PE) and phosphatidylserine (PS) are all phosphoglycerides, which are important components of cell membranes and are the basis of cellular metabolism, energy metabolism and signal transmission [ 39 ]. Lysophospholipids are a class of biologically active signaling lipids produced by phospholipase-mediated hydrolysis of membrane phospholipids (PLs) and sphingolipids (SLs) [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A rapidly evolving area in metabolism is evaluation of genetics and bioactive metabolites using single cell and tissue omics approaches. Frontiers in Metabolic Physiology has already published findings using omic approaches ( Hao et al, 2022 ; Li et al, 2022 ; McRae et al, 2022 ). The ability to handle and analyze this data in a manner that allows for clinical translation will be critical.…”
Section: Future Directionsmentioning
confidence: 99%